2015
DOI: 10.1039/c5cp02674a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual domain movement in a multidomain protein in the presence of macromolecular crowders

Abstract: Domain movements play a fundamental and critical role in the specific biological function that multidomain proteins have evolved to perform. A significant amount of research has been carried out to investigate the effects of macromolecular crowding agents, mostly on single domain proteins, thereby furthering our appreciation for the crowding phenomenon. However similar studies on proteins having multiple domains are relatively scarce. Using the plasma protein human serum albumin (HSA) as the protein of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…39,40 On the other hand, for dextran-6, there was a surprising increase in the distance between domain-I and domain-II. 39 In another contribution, they reported that the solvation dynamics of domain-I of HSA depends highly on the concentration of the crowder, owing mainly to the stiffness of the protein matrix. 41 In a recent article, Samanta et al concluded that in the presence of polyethylene glycol (PEG), another type of popular crowder, the α-helicity of HSA increases to a considerable extent.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…39,40 On the other hand, for dextran-6, there was a surprising increase in the distance between domain-I and domain-II. 39 In another contribution, they reported that the solvation dynamics of domain-I of HSA depends highly on the concentration of the crowder, owing mainly to the stiffness of the protein matrix. 41 In a recent article, Samanta et al concluded that in the presence of polyethylene glycol (PEG), another type of popular crowder, the α-helicity of HSA increases to a considerable extent.…”
mentioning
confidence: 95%
“…HSA is the most abundant transport protein in the human body. , It is a large multidomain protein with three distinct domains, namely, domains I, II, and III . All of these domains are responsible for binding and transporting different classes of molecules like drugs, enzymes, hormones, carbohydrates, etc. There are several reports on the behavior of HSA in the crowded environment in recent years. Singh et al monitored the tryptophan fluorescence intensity of HSA as a function of the extent of crowding . They have concluded that the quenching of tryptophan fluorescence by a crowder is mainly static in nature and that dextran-6 exhibits maximum quenching owing to its highest excluded volume by dextran-6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of crowding macromolecules has been shown to affect various protein processes, including protein-protein interactions, protein aggregation, and protein folding (3)(4)(5)(6). In protein folding, although crowdinginduced changes in the folded state have been reported (7), the observed stabilization of the folded state under crowded conditions is commonly attributed to destabilization of the unfolded state of the protein (8)(9)(10). The primary effect of crowding is the reduction of the volume available to proteins, which results in excluded volume effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…Serum proteins are the most abundant proteins present in the blood plasma accounting for over 50% of total protein content . Human serum albumin (HSA) being the avid transporter of fatty acids, different exogenous and endogenous drug molecules, it is important to study the interaction of the compounds with the serum proteins. In this work we examined the interactions of the solids 1–4 with bovine serum albumin (BSA) which has 67% of sequence homology to HSA .…”
Section: Resultsmentioning
confidence: 99%